Possibility of sweet corn synthetic seed production - P. Thobunluepop (2018)
Somatic embryogenesis in sweet corn has been reported by a number of workers. However, the knowledge maintaining storage life, vigor and viability of these somatic embryos are limited. A model system of synchronous somatic embryos production combined with encapsulation to synthetic seed was studied in sweet corn (Zea mays var. saccharata). In this study immature zygotic embryo cultured on N6 medium, contained 2, 4-D 2 mg L-1 and sucrose 60 g L-1 form the embryogenic callus. Higher 2, 4-D levels did not show increasing in inducing embryogenic callus. If the concentration of 2, 4-D decreased globular-stage, somatic zygote form the roots. Somatic embryo develop without surrounding nutritive tissues and protective seed coat has been devoted to causing somatic embryos to functionally mimic embryo, then was encapsulated by 3% (w/v) sodium alginate with 4-6 mm in diameter. It was found that when synthetic seed were treated with 60 g L-1 sucrose and stored at 15±2 degree Celsius for 2 weeks, the survival rate of synthetic seed were 44%, after 8 days of germination test, it was found that there were 91% of which were normal seedling and 9% were abnormal seedling. This result indicated that there is a possibility in sweet corn synthetic seed production. Anyhow, more research for better technique are further required. © 2009 Asian Network for Scientific Information.